Comparison of humpback whale (Megaptera novaeangliae) songs in the southern Indian Ocean indicates limited exchange between populations wintering off Madagascar and Western Australia - McCauley, Robert; Murray, Anita; Cerchio, S.; Jenner, Curt; Razafindrakoto, Y.; Coughran, Doug; McKay, S.; Rosenbaum, Howard (International Whaling Commission, 2009)
The definition of stock structure, as designated by the International Whaling Commission, is a critical matter in the conservation of Southern Hemisphere humpback whales (Megaptera novaeangliae). The difficulty lies in defining stocks in such a way that demographically isolated subpopulations are protected from extirpation. One methodology used to determine stock structure in the Northern Hemisphere is song comparisons between one or more breeding assemblages. Song comparisons are an indirect test of whether or not seasonally isolated breeding populations are interacting during the migratory cycle, thereby creating potential for genetic exchange. Song comparisons in the Northern Hemisphere show that whales within an ocean basin sing similar songs across different breeding areas as a result of cultural transmission, whereas geographically isolated populations in different ocean basins sing songs with very different content. Aural and visual analysis of song was used to determine similarity in song content between breeding populations along the coasts of Madagascar and Western Australia. Fifteen individuals were recorded in Madagascar from July-August 2006. Three individuals plus ~2 hours of data logger recordings (resulting from a sampling scheme of recording 6:48 minutes every fifteen minutes over a total of four hours) was gathered in Western Australia from September-October 2006. Madagascar and Western Australia song shared only one theme out of eleven, whereas each population had four and six private themes, respectively. The co-occurrence of one theme indicates that these stocks overlap at some point during the migratory cycle. However, compared to other intra-ocean song comparisons, these populations differ substantially in the amount of overlapping song content. Previous analysis of Western Australia song showed that this population is capable of under going rapid song transformations within one year, which may have caused the unusually low amount of song similarity with Madagascar. Alternatively, the lack of song similarity, beyond that of one common theme between Madagascar and Western Australia, maybe the result of a greater or equal amount of interaction between inter-ocean breeding stocks than there is between whales within the southern Indian Ocean. Evidence for interoceanic migration can be found in both the Madagascar and Western Australian breeding stocks.